“Genese” und “Komposition” in Vicos De uno - Giuseppe D’Anna (Laboratorio dell'ISPF, 2016)
[“Genesis” and “Composition” in Vico’s “De uno”]. The aim of this paper is to show the importance of the concepts of “genesis” and “composition” in Vico’s De uno. Using these two concepts Vico dynamizes the idea of essence and, in opposition to modern rationalism, he transforms it in a historical process, thus preparing the way to the concept of “nascimento” and to the theory of history of the Scienza nuova.